Accelerating wastewater-based SARS-CoV-2 surveillance using a mobile laboratory in mixed infrastructure regions - Amirmohammad Sakhaei; Soroosh Torabi; Mohammad Dehghan Banadaki; Alexus Rockward; William D. Strike; Soroush Farahbakhsh; David Graf; August Bodin; Amanda Muzzey; Riley Lang; Sara Ignoffo; Sean Haley; et al. (Science of The Total Environment, 2026)

Impact of salinity origin on microbial communities in saline springs within the Illinois Basin, USA - Linduo Zhao; Hongbo Shao; Li Zhang; Samuel V. Panno; Walton R. Kelly; Tzu‐Yu Lin; Wen‐Tso Liu; Theodore M. Flynn; Peter Berger (Environmental Microbiology, 2022)
Saline springs within the Illinois Basin result from the discharge of deep‐seated evaporated seawater (brine) and likely contain diverse and complex microbial communities that are poorly understood. In this study, seven saline/mineral springs with different geochemical characteristics and salinity origins were investigated using geochemical and molecular microbiological analyses to reveal the composition of microbial communities inhabiting springs and their key controlling factors. The 16S rRNA sequencing results demonstrated that each spring harbours a unique microbial community influenced by its geochemical properties and subsurface conditions. The microbial communities in springs that originated from Cambrian/Ordovician strata, which are deep confined units that have limited recharge from overlying formations, share a greater similarity in community composition and have a higher species richness and more overlapped taxa than those that originated from shallower Pennsylvanian strata, which are subject to extensive regional surface and groundwater recharge. The microbial distribution along the spring flow paths at the surface indicates that 59.8%–94.2% of total sequences in sedimentary samples originated from spring water, highlighting the role of springs in influencing microbiota in the immediate terrestrial environment. The results indicate that the springs introduce microbiota with a high biodiversity into surface terrestrial or aquatic ecosystems, potentially affecting microbial reservoirs in downstream ecosystems.

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Do motor plans affect sensorimotor state estimates during temporal decision-making with crossed vs. uncrossed hands? Failure to replicate the dynamic crossed-hand effect - Theodore Ching-Kong Cheung; Lin Lawrence Guo; Adam Frost; Christina F. Pereira; Matthias Niemeier (Experimental Brain Research, 2022)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Correction to: Functional near-infrared spectroscopy (fNIRS) brain imaging of multi-sensory integration during computerized dynamic posturography in middle-aged and older adults - Chia-Cheng Lin; Jeffrey W. Barker; Patrick J. Sparto; Joseph M. Furman; Theodore J. Huppert (Experimental Brain Research, 2018)

Functional near-infrared spectroscopy (fNIRS) brain imaging of multi-sensory integration during computerized dynamic posturography in middle-aged and older adults - Chia-Cheng Lin; Jeffrey W. Barker; Patrick J. Sparto; Joseph M. Furman; Theodore J. Huppert (Experimental Brain Research, 2017)

A Role for Low Density Lipoprotein Receptor-Related Protein 1 in the Cellular Uptake of Tissue Plasminogen Activator in the Lungs - Swan Lin; Jennifer Racz; Melissa F. Tai; Kristina M. Brooks; Phillip Rzeczycki; Lauren J. Heath; Michael W. Newstead; Theodore J. Standiford; Gus R. Rosania; Kathleen A. Stringer (Pharmaceutical Research, 2016)

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)